Music therapy improves social interaction and verbal communication skill among children with autism spectrum disorder: A systematic review and meta-analysis - Amirah, Shakira; Abdurrahman, Muhammad F.; Akbar, Raihan F. A.; Mulya, Intan C. (Narra Sains Indonesia, 2023)
The incidence of Autism Spectrum Disorder (ASD) is constantly increasing, in which 6 of 1000 ASD children are from Asia. Music therapy as a developing alternative is believed to improve communication and expression skills in children with ASD. Unfortunately, no specific meta-analysis has evaluated social interaction and verbal communication skills in children with ASD. Therefore, the aim of this meta-analysis was to evaluate music therapy in children with ASD. We performed a comprehensive literature review on PubMed, Scopus, Embase, Wiley, and Proquest to study the efficacy of music therapy as an ASD management therapy until October 20th, 2022. Twenty-three randomized controlled trials involving patients with ASD, where 1129 patients were assigned in the intervention group and 759 patients – in the control group, were included in qualitative and quantitative analysis. The pooled estimates revealed that music therapy increased the social interaction score with mean difference (MD)=2.08 (95% confidence interval [CI]: 0.35–3.81; p<0.02), social interaction score based on Autism Diagnostic Observation Schedule with MD: 0.77 (95% CI: 0.03–1.51; p<0.04), verbal communication skill based on Autism Diagnostic Interview-Revised with MD=0.90 (95% CI: 0.79–1.00, p<0.01). In conclusion, music therapy has excellent efficacy and strong potency as a part of ASD management. Nevertheless, more clinical trials with similar parameters are still required to confirm these findings.